TOWARDS RE-WRITING JAPANESE TEXTBOOKS FOR ELEMENTARY, INTERMEDIATE AND ADVANCED LEVELS TO SUIT THE TEACHING AND LEARNING CONDITIONS OF VIETNAM (IN THE CONNECTION WITH THE PROGRAM OF POST-GRADUATE STUDIES (Journal of Foreign Language Studies, 2008)
.